Increased Visual Perception in Night-Time Driving Conditions and/or Reduced Optical Visibility - Pašagić, Senka; Pašagić, Jasmina; Lovretić, Mihael (Promet - Traffic&Transportation, 2012)
The paper presents the significance of visual perception forthe safety of traffic participants. The essential guideline of visualperception is visibility, which is severely reduced innight-time driving conditions and/or conditions of reduced opticalvisibility. In order to increase the visibility in such conditionsa thermovision system has been developed, i.e. IR (infrared)system. The operating principle as well as the significanceof the new opto-electronic systems which in crease the visibilityat night and/or conditions of reduced optical visibility havebeen summarised in this paper. Based on the knowledge of theoperating principles it is possible to evaluate CO!Tectly the feasibilityof such IR systems.